2011
DOI: 10.7763/ijssh.2011.v1.7
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Associated Factors in Parents of Children with Cancer

Abstract: Abstract-Introduction: Diagnosis of cancer in children poses a challenging situation for parents to cope with. Method: Seventy-nine (N = 79) parents whose children are receiving treatment for cancer in Hospital Universiti Sains Malaysia participated in this cross-sectional descriptive study. They completed a set questionnaire measuring their level of anxiety and stress, knowledge about cancer, and amount of activities they perform with or for the child to enhance the child's coping abilities, in addition to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…A timeline of parental quality of life is seen (10), with most psychological distress at the point of diagnosis. Significant distress remains during treatment (1,16), correlating positively with the intensity of treatment (3) and especially chemotherapy (17). A review in Australia noted that completion of treatment can provoke intensified parental anxiety and additional stress as parents lose the security of the treatment regime and fear recurrence or relapse.…”
Section: Time Profile Of Hrqol and Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…A timeline of parental quality of life is seen (10), with most psychological distress at the point of diagnosis. Significant distress remains during treatment (1,16), correlating positively with the intensity of treatment (3) and especially chemotherapy (17). A review in Australia noted that completion of treatment can provoke intensified parental anxiety and additional stress as parents lose the security of the treatment regime and fear recurrence or relapse.…”
Section: Time Profile Of Hrqol and Stressmentioning
confidence: 99%
“…The child's behaviour and care-giving demands also reduce parental physical and mental health (4,23). Knowledge of the cancer decreased the stress experienced by Malaysian mothers (17), while better parental health habits (sleeping and diet) were protective in Canadian mothers (10). Optimism correlated with better satisfaction with life, anxiety, depression and perceptions of health for British parents (6).…”
Section: Aggravating and Protective Factorsmentioning
confidence: 99%
“…[ 4 ] A study among Hong Kong Chinese families suggested that knowing more about disease did not necessarily result in increased fear among parents. [ 5 ] On the other hand, providing adequate information has found to reduce uncertainty and help parents regain a sense of control over the situation pertaining to their child's illness, thus facilitating better coping.…”
Section: Discussionmentioning
confidence: 99%
“…A study from Malaysia showed that parents with higher level of education showed better cancer knowledge, and had lesser stress and anxiety. [ 5 ] A few studies evaluating the impacts of education and socioeconomic status of parents on pediatric cancer survival rates have shown that these constructs may influence treatment understanding and risk for psychological distress. [ 6 ] Contrary to this, other researchers have found that mothers' education level was not significantly correlated with cancer-related stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation